2024
DOI: 10.1182/bloodadvances.2023011687
|View full text |Cite
|
Sign up to set email alerts
|

Distinct peripheral T-cell and NK-cell profiles in HGBL-MYC/BCL2 vs patients with DLBCL NOS

A. Vera de Jonge,
Carolien Duetz,
Wassilis S. C. Bruins
et al.

Abstract: High-grade B-cell lymphoma patients with MYC and BCL2 rearrangements (HGBL-MYC/BCL2) respond poorly to immuno-chemotherapy compared to diffuse large B-cell lymphoma not otherwise specified (DLBCL NOS) patients without a MYC rearrangement. This suggests a negative impact of lymphoma-intrinsic MYC on the immune system. To investigate this, we compared circulating T-cells and NK-cells of HGBL-MYC/BCL2 patients (n=66), DLBCL NOS patients (n=53) and age-matched healthy donors (HDs, n=16) by flow cytometry and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Lipids and lipid metabolism play a crucial role in various non-apoptotic cell death pathways, and alterations in lipid metabolism may initiate mitochondrial autophagy, leading to necrotizing apoptosis [ 32 ]. Vera de Jonge et al identified peripheral T cell and NK cell characteristics distinct from DLBCL patients in HGBL-MYC/BCL2 [ 33 ]. MORTALIN regulates the release of Ca2+ from the endoplasmic reticulum through the mitochondrial membrane and promotes the down-regulation of FAS in DLBCL cells, making it a potential drug for treating DLBCL [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipids and lipid metabolism play a crucial role in various non-apoptotic cell death pathways, and alterations in lipid metabolism may initiate mitochondrial autophagy, leading to necrotizing apoptosis [ 32 ]. Vera de Jonge et al identified peripheral T cell and NK cell characteristics distinct from DLBCL patients in HGBL-MYC/BCL2 [ 33 ]. MORTALIN regulates the release of Ca2+ from the endoplasmic reticulum through the mitochondrial membrane and promotes the down-regulation of FAS in DLBCL cells, making it a potential drug for treating DLBCL [ 34 ].…”
Section: Discussionmentioning
confidence: 99%